2017
DOI: 10.1371/journal.pone.0180086
|View full text |Cite
|
Sign up to set email alerts
|

The urine metabolome differs between lean and overweight Labrador Retriever dogs during a feed-challenge

Abstract: Obesity in dogs is an increasing problem and better knowledge of the metabolism of overweight dogs is needed. Identification of molecular changes related to overweight may lead to new methods to improve obesity prevention and treatment. The aim of the study was firstly to investigate whether Nuclear Magnetic Resonance (NMR) based metabolomics could be used to differentiate postprandial from fasting urine in dogs, and secondly to investigate whether metabolite profiles differ between lean and overweight dogs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…To date, only one study determined allantoin as a biomarker in humans, which aimed to predict gestational diabetes development using MS approach. This study showed higher levels of allantoin in the group of women with higher risk to develop diabetes [77].…”
Section: Uric Acid and Allantoinsupporting
confidence: 54%
“…To date, only one study determined allantoin as a biomarker in humans, which aimed to predict gestational diabetes development using MS approach. This study showed higher levels of allantoin in the group of women with higher risk to develop diabetes [77].…”
Section: Uric Acid and Allantoinsupporting
confidence: 54%
“…First, this pilot exploratory study has been performed in a relatively small and highly homogenous population of intact female domestic cats maintained under experimentally controlled conditions. Many extrinsic factors have been shown to affect the urinary metabolome including the gastrointestinal microbiota [57], [58], obesity/diet [59], [60], age [61], exercise [62], diurnal variation [63], gender [61], and environmental chemicals [64]. The elegance of the study reported here lies in the fact that we tested the metabolite selection using a separate data set generated during an independent study that included cats from a different breeder source, hosting conditions, and sampling times which increases the validity of this study's findings.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies, with which the dogs were awarded table scraps, treats or dog chews did not differ between body condition groups (Table 1). Serum leptin concentration was used to verify the clinical body condition grouping [30].…”
Section: Methodsmentioning
confidence: 99%
“…In humans, the postprandial metabolome is less variable than fasting and can generate more information about important metabolic changes that would otherwise be difficult to detect [2529]. In overweight dogs, we have previously found more pronounced metabolic variations in postprandial compared to fasting urine [30]. Therefore, plasma metabolomics in combination with a meal challenge has the potential to enhance the understanding of canine metabolism and to detect subtle metabolic variations related to overweightness in dogs.…”
Section: Introductionmentioning
confidence: 99%